Ecological and Health Risks of Polycyclic Aromatic Hydrocarbons in Particulate Matter in Chinese Cities - Yongfu Wu; Yuan Meng; Han Zhang; Lianglu Hao; Tao Zeng; Yan Shi; Yunhe Chen; Ni Qiao; Yibin Ren (GeoHealth)
Abstract During the first two decades of the 21st century, the level of polycyclic aromatic hydrocarbon (PAH) pollution in urban atmospheric particulate matter (PM) in China significantly increased. By combining data from more than 6,695 individual samples covering 89 typical cities (population > 0.5 million people) across China, this study focuses on evaluating the health risks to urban residents and the ecological risks to the surrounding environment from PAHs in PM using the methods of the United States Environmental Protection Agency and sediment quality standards. The PAH contents and contamination levels in Central China (CC) were lower than those in South China (SC) and North China (NC). NC exhibited the most severe PAH pollution and greatest ecological risk, while CC had the highest population density and gross domestic product. The incremental lifetime cancer risk and hazard index values for people in NC were greater than those for people in CC and SC, and the health risk increased with increasing latitude. Based on ecological risk criteria and standard assessment methods, PAHs in PM in China pose a potential ecological risk, and the risk of harmful biological effects follows the order of NC > CC > SC. Given the significant risks of PAHs to people, animals and plants at both the national and global scales, under the guidance of the One Health concept of the World Health Organization, it is necessary to comprehensively manage PAHs in PM and reduce their threats to humans and ecosystems.